Rates and causative pathogens of surgical site infections attributed to liver transplant procedures and other hepatic, biliary, or pancreatic procedures, 2015‐2018. Issue 4 (23rd March 2021) - Chea, Nora; Sapiano, Mathew R. P.; Zhou, Liang; Epstein, Lauren; Guh, Alice; Edwards, Jonathan R.; Allen‐Bridson, Katherine; Russo, Victoria; Watkins, Jennifer; Pouch, Stephanie M.; Magill, Shelley S.
Abstract: Liver transplant recipients are at high risk for surgical site infections (SSIs). Limited data are available on SSI epidemiology following liver transplant procedures (LTPs). We analyzed data on SSIs from 2015 to 2018 reported to CDC's National Healthcare Safety Network to determine rates, pathogen distribution, and antimicrobial resistance after LTPs and other hepatic, biliary, or pancreatic procedures (BILIs). LTP and BILI SSI rates were 5.7% and 5.9%, respectively. The odds of SSI after LTP were lower than after BILI (adjusted odds ratio = 0.70, 95% confidence interval 0.57‐0.85). Among LTP SSIs, 43.1% were caused by Enterococcus spp., 17.2% by Candida spp., and 15.0% by coagulase‐negative Staphylococcus spp. (CNS). Percentages of SSIs caused by Enterococcus faecium or CNS were higher after LTPs than BILIs, whereas percentages of SSIs caused by Enterobacteriaceae, Enterococcus faecalis, or viridans streptococci were higher after BILIs. Antimicrobial resistance was common in LTP SSI pathogens, including E. faecium (69.4% vancomycin resistant); Escherichia coli (68.8% fluoroquinolone non‐susceptible and 44.7% extended spectrum cephalosporin [ESC] non‐susceptible); and Klebsiella pneumoniae and K. oxytoca (39.4% fluoroquinolone non‐susceptible and 54.5% ESC non‐susceptible). National LTP SSI pathogen and resistance data can help prioritize studies to determine effective interventions to prevent SSIs and reduce antimicrobial resistance in liver transplant recipients.